Rhodomyrtals A-D, four unusual phloroglucinol-sesquiterpene adducts from Rhodomyrtus psidioides - Shou, Qingyao; Smith, Joshua E.; Mon, Htwe; Brkljaca, Zlatko; Smith, Ana-Suncana; Smith, David M.; Griesser, Hans J.; Wohlmuth, Hans (RSC Advances, 2014)
Four novel compounds, rhodomyrtals A-D (1-4), with two unprecendented carbon frameworks of phloroglucinol coupled eudesmane, together with the known compound eucalyptin A (5) have been isolated from the leaves of the Australian plant Rhodomyrtus psidioides. The structures of compounds 1-4 were elucidated by spectroscopic analysis and ECD calculations. Some of the compounds showed good antibacterial activity against selected Gram-positive strains.
Keywords: TOMENTOSA AITON HASSK.; STAPHYLOCOCCUS-AUREUS; EUCALYPTUS-GLOBULUS; MYRTACEAE; CANDIDATE; LEAVES